Cardiovascular morbidity and mortality after liver transplantation: The protective role of mycophenolate mofetil. Issue 4 (April 2017) - D'Avola, Delia; Cuervas‐Mons, Valentín; Martí, Josep; Ortiz de Urbina, Jorge; Lladó, Laura; Jimenez, Carlos; Otero, Esteban; Suarez, Francisco; Rodrigo, Juan M.; Gómez, Miguel‐Angel; Fraga, Enrique; Lopez, Pedro; et al.
Abstract : Cardiovascular (CV) diseases are recognized longterm causes of death after liver transplantation (LT). The objective of this multicenter study was to analyze the prevalence and the evolution of CV risk factors and CV morbidity and mortality in 1819 LT recipients along 5 years after LT. The influence of baseline variables on survival, morbidity, and mortality was studied. There was a continuous and significant increase of the prevalence of all the CV risk factors (except smoking) after LT. CV diseases were the fourth cause of mortality in the 5 years after LT, causing 12% of deaths during the follow‐up. Most CV events (39%) occurred in the first year after LT. Preexisting CV risk factors such as age, pre‐LT CV events, diabetes, metabolic syndrome, and hyperuricemia, and mycophenolate‐free immunosuppressive therapy, increased post‐LT CV morbidity and mortality. The development of new‐onset CV risk factors after LT, such as dyslipidemia and obesity, independently affected late CV morbidity and mortality. Tacrolimus and steroids increased the risk of posttransplant diabetes, whereas cyclosporine increased the risk of arterial hypertension, dyslipidemia, and metabolic syndrome. In conclusion, CV complications and CV mortality are frequent in LT recipients. Preexisting CV risk factors, immunosuppressive drugs, but also the early new onset of obesity and dyslipidemia after LT play an important role on late CV complications. A strict metabolic control in the immediate post‐LT period is advisable for improving CV risk of LT recipients. Liver Transplantation 23 498–509 2017 AASLD.